Risk analysis of cyber-campus modules (security guidelines of electronic academic assets) - Ibrahim, Subariah; Salleh, Mazleena; Ithin, Norafida; Ahmad, Rabiah (Faculty of Computer Science and Information system, 2003)
As the country moves into the Information Age, the use of Information and Communication Technology (ICT) has become a ubiquitous activity in the university departments for academic and administrative purposes. University academic information resources are valuable assets and the security of these assets should be managed properly. Without proper security measures and controls may result in the compromise, improper modification, or destruction of the information resources. This project focuses in outlining the security guideline that can be followed by academic staffs and others who are responsible for the security of electronic information in a university environment. The guideline addresses issues such as choosing good passwords, preventing virus attacks, email security, pc intrusion and administrative responsibilities for the users and administrators who manage computers and networks. Risk analysis technique is used as a guidance in order to come out with the security guideline that is suitable for FSKSM. The guideline is simple and short enough so that it is easy to understand and followed by all levels of staffs. The security guideline formulated can be used as a starting point in drafting a security policy at UTM. With the application of security policy in the academic environment, the security of academic assets can be enhanced and the network as a whole can be trusted.